Knowledge, adherence to non-pharmaceutical interventions, and impact of COVID-19 lockdown among traders in Ibadan, Nigeria: Knowledge and adherence to non-pharmaceutical interventions among traders in Ibadan (African Journal of Biomedical Research, 2021)
The COVID-19 is a major public health problem in Nigeria. Not enough is known about knowledge, adherence to non-pharmaceutical interventions, and impact of COVID-19 lockdown measures among traders in the informal sector in Nigeria. To address these gaps in knowledge, 383 traders in Alesinloye market in Ibadan metropolis were interviewed using a questionnaire. In-depth interviews were also conducted with 10 leaders of trader associations. There are slightly more females (51.2%) than male (48.8%) participants. The mean age was 42.9 years. The mean COVID-19 knowledge score is 9.4 out of 10. More females (9.5) than male (9.4) have higher mean knowledge score (p=0.02). Frequent hand washing with soap and water is the most frequently reported NPI adhered to (72.1%); the respective percentages that practiced physical distancing and wearing face mask are 44% and 33.3%. More females than males significantly practiced NPI (p=0.01). The main impact of lockdown measures include reduction in income (97.4%) and inability to restock items (79.1%). Most respondents (63.4%) reported that a member of their household skipped a meal due to lack of money to get food. Qualitative data reveal that a perception that COVID-19 was no longer a public health problem was responsible to the less-than-optimal adherence to NPI. The study participants are well informed about COVID-19, but many did not practice what they know. Female respondents had better knowledge and adherence to NPI. A gendered approach is recommended to motivate men for better adherence.